Efficiency and effectiveness of zakat distribution for socio-economic benefits and wellbeing of zakat recipients - Rosman, Romzie; Othman, Anwar Hasan Abdullah; Redzuan, Nur Harena; Sharofiddin, Ashurov; Mohamad, Muslim Har Sani; Engku Ali, Engku Rabiah Adawiah (2020)
The institution of zakat has played an important role in the economy. The efficiency and effectiveness of zakat collection and distribution contribute to the socio-economic wellbeing of the zakat recipients. However, even after receiving the zakat funds, the zakat recipients still have to live in poverty. The zakat institutions are unable to provide them with the necessary tools and eco-system that can sustain them out of poverty to improve their socio-economic wellbeing in terms of their health, education, and financial literacy. Therefore, tis research aims to critically review the relevant literature to explain the issue and challenges of the current zakat collection and distribution; and to propose an efficient, effective and sustainable zakat distribution model that reflects the needs of zakat recipients in relation to income enhancement, health care, education, and financial literacy. The objectives of the research are: (1) to identify the socio-economic challenges of zakat distribution model that hinders the zakat recipient's socio-economic wellbeing in term of education, health and financial literacy; and (2) to propose an efficient and effective channel for zakat distribution model in improving zakat recipient's socio-economic wellbeing. A new zakat distribution model need to be established to improve the zakat recipient's socio-economic wellbeing in Malaysia. Based on the research, theoretical and practical contributions are expected to support both Maqasid Shariah and Sustainable Development Goals.